Fabricating Modern Societies: Education, Bodies, and Minds in the Age of Steel - Priem, Karin; Herman, Frederik (Studies in Global Social History, 2019)
Fabricating Modern Societies: Education, Bodies, and Minds in the Age of Steel offers new interdisciplinary and transnational perspectives on industrialization and societal transformation in early-twentieth-century Luxembourg by analyzing social-educational initiatives and various technologies of modernity and their effects. Readership: All interested in the social, educational, cultural-material, technological, and economic transformations of modern industrialist societies and related technologies of mediatization, mechanization, and scientification at the beginning of the twentieth century.